Kajian Teologis terhadap Tradisi Manulangi dalam Budaya Batak Toba - Tolop Marbun (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2023)
According to Batak Toba's ancestors, The manulangi ritual is one of the ways to give the highest respect to parents. Since the manulangi tradition is the ancestor's legacy, few people assume it is irrelevant because there are many ways to honour parents. Some sectarians think all Batak Toba rituals are sins and against the Bible. This research aims to discover the theological values in the manulangi tradition for Batak Toba, which still keeps the manulangi ritual in Christians' values. The method is qualitative research with a literature study. The data are collected from works of literature that are related to the topic. All literature will be analyzed with the content analytics method to build frames of thinking. Lastly, the author will apply the theological approach to the manulangi ritual to discover theological value. All data is displayed descriptively. The manulangi tradition is relevant to the great; the first commandment is to love God and neighbours. Loving God through the manulangi ritual is to glorify God and obey God. Loving neighbours through the manulangi ritual is to bless one another, restore relationships with neighbours, and bear one another's burdens.